Fostering transition to adulthood for young Australian males: an exploratory study of Men's Sheds’ intergenerational mentoring programmes - Rahja, M.; Scanlan, J.; Wilson, N.; Cordier, Reinie (Wiley-Blackwell Publishing Asia, 2016)
Introduction: Men's Sheds are community spaces where socialisation occurs alongside participation in meaningful activities. Shed activities and socialisation make them useful for supporting transition to adulthood of ‘at-risk’ young people through meaningful occupations. Many sheds have implemented intergenerational mentoring programmes. However, many programmes are established on an ad-hoc basis without specific attention to factors that may support effective and sustainable outcomes. We aimed to inform future programmes by exploring different programmes to provide insight into the purpose, design and programme characteristics that are perceived as beneficial for young males. Method: Four Sydney-based sheds providing intergenerational mentoring programmes were selected. We interviewed shed coordinators, mentors and mentees to explore their perceptions of programme characteristics that supported mentees’ transition to adulthood. Thematic analysis techniques were used to first analyse and understand the unique context of each programme and these were then merged and integrated to identify the most helpful aspects of these mentoring programmes. Results: Mentor attitude towards the mentees, freedom to make independent choices and the nature and perceived usefulness of the project were considered the most significant characteristics of these programmes. Conclusion: This was the first known examination of the different characteristics of Men's Sheds intergenerational mentoring programmes. On the basis of our findings, we have made recommendations to help guide the planning and implementation of future programmes. While our findings largely support previous research on mentoring programmes, findings from this study suggest that ‘expert skills’ may not be as important as mentor attitude to working with the mentees.